Ответ:
не уверена, что правильно, но пыталась
1039
a) (a+2)(a-2) - a(a-5) = a² - 4 - a² + 5a = 5a - 4
б) (a-3)(3+a) + a(7-a) = a² - 9 + 7a - a² = 7a - 9
в) (b-4)(b+4) - (b-3)(b+5) = b² - 16 - b² - 5b + 3b + 15 = -1 - 2b
г) (b+8)(b-6) - (b-7)(b+7) = b² - 6b + 8b - 48 - b² + 49 = 2b + 1
д) (c-1)(c+1) + (c-9)(c+9) = c² - 1 + c² - 81 = 2c² - 82
е) (5+c)(c-5) - (c-10)(c+10) = c² - 25 - c² + 100 = 125
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
не уверена, что правильно, но пыталась
Ответ:
1039
a) (a+2)(a-2) - a(a-5) = a² - 4 - a² + 5a = 5a - 4
б) (a-3)(3+a) + a(7-a) = a² - 9 + 7a - a² = 7a - 9
в) (b-4)(b+4) - (b-3)(b+5) = b² - 16 - b² - 5b + 3b + 15 = -1 - 2b
г) (b+8)(b-6) - (b-7)(b+7) = b² - 6b + 8b - 48 - b² + 49 = 2b + 1
д) (c-1)(c+1) + (c-9)(c+9) = c² - 1 + c² - 81 = 2c² - 82
е) (5+c)(c-5) - (c-10)(c+10) = c² - 25 - c² + 100 = 125